Hakikat Bidaah Hasanah dan Sayyi’ah Menurut Ahli Akademik di IPTA Malaysia: The Concept of Hasanah and Sayyi’ah Bidaah According to Academics at Malaysian Public Higher Education Institutions - Abdul Halim, Amran (Journal Of Hadith Studies, 2024)
This paper aims to explore the perspectives of academic scholars on Imam al-Shafi’i’s categorization of bidaah into hasanah (good) and sayyi’ah (bad). The selected scholars are from the Academy of Islamic Studies at Universiti Malaya, Universiti Kebangsaan Malaysia, Universiti Sains Islam Malaysia, and Universiti Islam Antarabangsa, representing various fields within Islamic Studies. The research employs a survey method, specifically using cluster sampling. The author distributed the survey forms to academic staff at these universities. Based on the descriptive analysis of the survey results, it can be concluded that the scholars possess a strong understanding of hadith and the concept of bidaah. They also perceive that the study of hadith is insufficiently emphasized within society. Analyzing the overall responses, particularly regarding the concept of bidaah as derived from the hadiths of Kutub al-Tis’ah, their views align closely with those of scholars such as al-Nawawi, al-Syatibi, Ibn Hajar al-‘Asqalani, and others. Consequently, these scholars are well-positioned to serve as references for the community in addressing issues related to bidaah, particularly those specializing in hadith. It is hoped that this paper will provide guidance to educators, institutions, religious departments, and others in contributing valuable knowledge to the Muslim community, enhancing their understanding of the hadith of the Prophet Muhammad (SAW), applying these teachings in their lives, and clarifying any confusion or misunderstandings regarding Imam al-Shafi’i’s categorization of bidaah.